Extended Monopole antenna Array with individual Shield (EMAS) coil: An improved monopole antenna design for brain imaging at 7 tesla MRI. Issue 6 (20th July 2015) - Woo, Myung‐Kyun; Hong, Suk‐Min; Lee, Jongho; Kang, Chang‐Ki; Park, Sung‐Yeon; Son, Young‐Don; Kim, Young‐Bo; Cho, Zang‐Hee
Abstract : Purpose: To propose a new Extended Monopole antenna Array with individual Shields (EMAS) coil that improves the B1 field coverage and uniformity along the z‐direction. Methods: To increase the spatial coverage of Monopole antenna Array (MA) coil, each monopole antenna was shielded and extended in length. Performance of this new coil, which is referred to as EMAS coil, was compared with the original MA coil and an Extended Monopole antenna Array coil with no shield (EMA). For comparison, flip angle, signal‐to‐noise ratio (SNR), and receive sensitivity maps were measured at multiple regions of interest (ROIs) in the brain. Results: The EMAS coil demonstrated substantially larger flip angle and receive sensitivity than the MA and EMA coils in the inferior aspect of the brain. In the brainstem ROI, for example, the flip angle in the EMAS coil was increased by 45.5% (or 60.0%) and the receive sensitivity was increased by 26.9% (or 14.9%), resulting in an SNR gain of 84.8% (or 76.3%) when compared with the MA coil (or EMA). Conclusion: The EMAS coil provided 25.7% (or 24.4%) more uniform B 1 + field distribution compared with the MA (or EMA) coil in sagittal. The EMAS coil successfully extended the imaging volume in lower part of the brain. Magn Reson Med 75:2566–2572, 2016. © 2015 Wiley Periodicals, Inc.